Mistletoe and Mr. Right - Morgenthaler, Sarah (Sourcebooks Casablanca, an imprint of Sourcebooks, 2020)
"How the moose (almost) stole Christmas. Lana Montgomery is everything the quirky small town of Moose Springs, Alaska, can't stand: a rich socialite with dreams of changing things for the better. But Lana's determined to prove that she belongs ... even if it means trading her stilettos for snow boots and tracking one of the town's hairiest Christmas mysteries: the Santa Moose, an antlered Grinch hell-bent on destroying every bit of holiday cheer (and tinsel) it can sink its teeth into. And really ... how hard could it be? The last few years have been tough on Rick Harding, and it's not getting any easier now that his dream girl's back in town. When Lana accidentally tranquilizes him instead of the Santa Moose, it's clear she needs help, fast ... and this could be his chance to finally catch her eye. It's an all-out Christmas war, but if they can nab that darn moose before it destroys the town, Rick and Lana might finally find a place where they both belong ... together"--